Programmed Molecular Assembly of Abrupt Crystalline Organic/Organic Heterointerfaces Yielding Metal‐Organic Framework Diodes with Large On‐Off Ratios. Issue 7 (21st January 2021) - Chandresh, Abhinav; Liu, Xiaojing; Wöll, Christof; Heinke, Lars
Abstract: Structurally well‐defined, crystalline organic/organic heterojunctions between C60 ‐ and anthracene‐based semiconductors are realized via layer‐by‐layer deposition of metal‐organic framework, MOF, thin films. As demonstrated by X‐ray diffraction, perfect epitaxy is achieved by adjusting the lattice constants of the two different MOFs. Deposition of top electrodes allows to fabricate p–n as well as n–p devices. Measurements of the electrical properties reveal the presence of high‐performance diodes, with a current on/off ratio of up to 6 orders of magnitude and an ideality factor close to unity. The crystalline nature of the abrupt organic/organic heterojunction provides the basis for a rational, simulation‐based optimization and tailoring of such organic semiconductor interfaces. Abstract : Crystalline abrupt organic/organic heterojunctions are presented. This is realized by incorporating semiconducting molecules, here anthracene and C60, in metal‐organic framework thin films fabricated in a layer‐by‐layer fashion forming bilayer films. The p–n‐junctions show strong diode performance with a current rectification of up to six orders of magnitude.